A dual‐AAV approach restores fast exocytosis and partially rescues auditory function in deaf otoferlin knock‐out mice. Issue 1 (3rd December 2018) - Al‐Moyed, Hanan; Cepeda, Andreia P; Jung, SangYong; Moser, Tobias; Kügler, Sebastian; Reisinger, Ellen
Abstract: Normal hearing and synaptic transmission at afferent auditory inner hair cell (IHC) synapses require otoferlin. Deafness DFNB9, caused by mutations in the OTOF gene encoding otoferlin, might be treated by transferring wild‐type otoferlin cDNA into IHCs, which is difficult due to the large size of this transgene. In this study, we generated two adeno‐associated viruses (AAVs), each containing half of the otoferlin cDNA. Co‐injecting these dual‐AAV2/6 half‐vectors into the cochleae of 6‐ to 7‐day‐old otoferlin knock‐out ( Otof −/− ) mice led to the expression of full‐length otoferlin in up to 50% of IHCs. In the cochlea, otoferlin was selectively expressed in auditory hair cells. Dual‐AAV transduction of Otof −/− IHCs fully restored fast exocytosis, while otoferlin‐dependent vesicle replenishment reached 35–50% of wild‐type levels. The loss of 40% of synaptic ribbons in these IHCs could not be prevented, indicating a role of otoferlin in early synapse maturation. Acoustic clicks evoked auditory brainstem responses with thresholds of 40–60 dB. Therefore, we propose that gene delivery mediated by dual‐AAV vectors might be suitable to treat deafness forms caused by mutations in large genes such as OTOF . Synopsis: Gene delivery of large genes exceeding the packing capacity of a single adeno‐associated virus (AAV) is challenging. Split‐AAV vectors can bypass this problem. This work offers the first application of split‐AAV gene therapy to the inner ear to restore hearing in a genetically deaf mouse model. The 6 kb‐long otoferlin coding sequence was split into two fragments and packaged into two separate AAV2/6 viruses which were co‐injected into cochleae of otoferlin knock‐out mice. Both the dual‐AAV trans‐splicing and the hybrid strategy led to re‐assembly of the two otoferlin cDNA fragments and expression of full‐length otoferlin. Otoferlin expression from dual‐AAVs was restricted to hair cells and reached ˜30% of wild type otoferlin protein levels in inner hair cells. In inner hair cells, fast exocytosis of the readily releasable pool of vesicles was fully recovered, and vesicle replenishment was restored to 35–50% of wild‐type controls. Auditory brainstem responses were present albeit with reduced wave amplitudes in dual‐AAV transduced otoferlin knock‐out mice and indicated hearing thresholds of 40–60 dB. Abstract : Gene delivery of large genes exceeding the packing capacity of a single adeno‐associated virus (AAV) is challenging. Split‐AAV vectors can bypass this problem. This work offers the first application of split‐AAV gene therapy to the inner ear to restore hearing in a genetically deaf mouse model.